Wybrane zagadnienia prawa autorskiego dotyczące tworzenia internetowych galerii sztuki (ze szczególnym uwzględnieniem wolności panoramy) - Jakimczuk, Ewa (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The impact of global digitalisation on art means that art is now more accessible than ever before and with its variety of online platforms and digital galleries it has the widest distribution ever. For many people, digital representation is and will remain the only way to experience art, thus questions need to be raised around acceptable usage of a digital method. Here are my thoughts on a subject of how “ freedom of panorama” is being applied in commercial and non-commercial environments, when digital images of otherwise publicly available art and objects are being used. Other areas covered here touch on issues such as intellectual rights of artists and creators, acceptable use of digital images, importance of references to sources, prime locations or institutions of art used in digital representations. As well as topics of commercial advantage and physical gains from using digital representation of publicly accessible art.